Modified microwave dielectric ceramic, preparation method and application thereof

CN122878115APending Publication Date: 2026-10-09QINGDAO JINGCHOU ELECTRONIC TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611080313.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-21
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

然而,四硼酸钠陶瓷在实际制备过程中存在烧结行为难以控制等问题

Benefits of technology

[0015]本发明提供了一种改性微波介质陶瓷的制备方法,包括以下步骤:将Na2B4O7与BaCuB2O5球磨混合,得到混合粉体;将所述混合粉体与粘结剂混合后依次进行造粒和挤压成型,得到陶瓷坯体;将所述陶瓷坯体烧结,得到改性微波介质陶瓷。在本发明中,将BaCuB2O5作为改性组分引入主晶相为Na2B4O7的陶瓷体系中,在烧结过程中,BaCuB2O5由于具有较低的熔融温度,可在烧结温度下形成少量液相,从而促进颗粒之间的接触、重排及物质迁移,提高烧结驱动力,加快陶瓷的烧结致密化进程;液相的存在有利于填充颗粒间孔隙,促进孔隙排除,降低陶瓷内部残余孔隙率,提高烧结体的相对密度,并获得更加均匀、致密的显微组织。同时,BaCuB2O5能够改善陶瓷烧结过程中晶粒的生长行为,使显微组织更加均匀,减少局部组织缺陷,从而降低由孔隙和组织不均匀引起的介电损耗,在保持Na2B4O7主体晶相稳定的基础上,提高微波介电性能。本发明的改性微波介质陶瓷的制备方法在不破坏Na2B4O7主晶相结构的前提下,对陶瓷的微观结构起到调控作用,有利于促进烧结过程中物质迁移和晶界结合,减少孔隙缺陷,使所得陶瓷材料组织更加致密、均匀,解决了四硼酸钠陶瓷存在的烧结行为难以控制,烧结后的陶瓷存在的孔隙率较高、微观结构不均匀以及晶界结合能力较弱的问题,得到的改性微波介质陶瓷介电常数低、介电损耗小、温稳介电性能好。实验结果表明,本发明的制备方法制备的改性微波介质陶瓷相对密度高达89.21%~94.74%;介电性能为:εr=3.85~4.87,Q×f=15042~23348GHz,τf=-38.4~-49.6ppm/℃,介电常数低、介电损耗小、温稳介电性能好。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122878115A_ABST
    Figure CN122878115A_ABST
Patent Text Reader

Abstract

The application provides a modified microwave dielectric ceramic and a preparation method and application thereof. The preparation method of the modified microwave dielectric ceramic comprises the following steps: Na2B4O7 is ball-milled and mixed with BaCuB2O5 to obtain a mixed powder; the mixed powder is mixed with a binder and then subjected to granulation and extrusion forming in sequence to obtain a ceramic body; and the ceramic body is sintered to obtain the modified microwave dielectric ceramic. In the application, BaCuB2O5 is introduced into the ceramic system of Na2B4O7, the microstructure of the ceramic is regulated without destroying the main crystal phase structure of Na2B4O7, the material migration and the grain boundary combination in the sintering process are promoted, the pore defects are reduced, the obtained ceramic material is more dense and uniform, the problem that the sintering behavior of the sodium tetraborate ceramic is difficult to control is solved, and the obtained modified microwave dielectric ceramic has low dielectric constant, small dielectric loss and good temperature-stable dielectric performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of microwave dielectric ceramic materials technology, specifically relating to a modified microwave dielectric ceramic, its preparation method, and its application. Background Technology

[0002] Microwave dielectric ceramics are key functional materials in modern wireless communication, satellite navigation, radar systems, and microwave antennas. Their dielectric constant, dielectric loss, and temperature-stable dielectric properties directly affect the miniaturization, operational stability, and energy transfer efficiency of these devices. As communication technologies evolve towards higher frequencies, greater integration, and lower power consumption, higher demands are placed on microwave dielectric ceramic materials in terms of low dielectric loss and stable dielectric properties.

[0003] Borate-based ceramics, due to the presence of [BO3] or [BO4] groups in their structure, typically exhibit low dielectric constants and good high-frequency response characteristics, making them promising candidates for application in microwave dielectric materials. However, sodium tetraborate ceramics face challenges in controlling sintering behavior during actual preparation. Sodium tetraborate has a narrow sintering temperature range, making it prone to softening, deformation, and even localized melting, hindering the production of structurally intact and dense ceramic bodies. Due to insufficient densification driving force, sintered ceramic samples often exhibit high porosity, inhomogeneous microstructure, and weak grain boundary bonding. Pores and a loose microstructure lead to numerous two-phase interfaces between the ceramic matrix and air, resulting in interfacial relaxation polarization under microwave alternating electric fields, significantly increasing the loss factor, raising tanδ, and substantially attenuating Q×f. Furthermore, the porous microstructure alters the overall thermal expansion behavior of the ceramic, causing excessive temperature drift at the resonant frequency and substandard device temperature stability, thus limiting the practical application of microwave dielectric ceramics in microwave dielectric devices. Summary of the Invention

[0004] The purpose of this invention is to provide a modified microwave dielectric ceramic, its preparation method, and its application. The modified microwave dielectric ceramic prepared by the preparation method provided by this invention has a low dielectric constant, low dielectric loss, and good temperature-stable dielectric properties.

[0005] To achieve the above-mentioned objectives, the present invention provides the following technical solution: This invention provides a method for preparing modified microwave dielectric ceramics, comprising the following steps: Na2B4O7 and BaCuB2O5 were ball-milled and mixed to obtain a mixed powder; The mixed powder is mixed with a binder and then granulated and extruded sequentially to obtain a ceramic green body. The ceramic blank is sintered to obtain a modified microwave dielectric ceramic.

[0006] Preferably, the mass of BaCuB2O5 is 1% to 5% of that of Na2B4O7.

[0007] Preferably, the particle size of the mixed powder is 80-100 mesh.

[0008] Preferably, the sintering temperature is 580~620℃ and the sintering time is 3~5h.

[0009] Preferably, the adhesive is removed by heating before sintering, the temperature of the adhesive removal is 490~510℃, and the time of adhesive removal is 1.5~2.5h.

[0010] Preferably, the adhesive is a polyvinyl alcohol aqueous solution with a mass fraction of 3-8%.

[0011] Preferably, the mass of the binder is 6-10% of the mixed powder.

[0012] The present invention also provides a modified microwave dielectric ceramic prepared by the preparation method described above, comprising Na2B4O7 and BaCuB2O5; wherein Na2B4O7 is the main crystalline phase and BaCuB2O5 is the second phase.

[0013] Preferably, the grain size of the BaCuB2O5 is 0.5~5μm.

[0014] The present invention also provides modified microwave dielectric ceramics prepared by the preparation method described above, or the application of modified microwave dielectric ceramics described above in microwave dielectric devices.

[0015] This invention provides a method for preparing modified microwave dielectric ceramics, comprising the following steps: ball milling and mixing Na₂B₄O₇ and BaCuB₂O₅ to obtain a mixed powder; mixing the mixed powder with a binder and then granulating and extruding it sequentially to obtain a ceramic green body; sintering the ceramic green body to obtain the modified microwave dielectric ceramic. In this invention, BaCuB₂O₅ is introduced as a modifying component into a ceramic system with Na₂B₄O₇ as the main crystalline phase. During sintering, BaCuB₂O₅, due to its low melting temperature, can form a small amount of liquid phase at the sintering temperature, thereby promoting contact, rearrangement, and mass migration between particles, increasing the sintering driving force, and accelerating the sintering densification process of the ceramic. The presence of the liquid phase is beneficial for filling the pores between particles, promoting pore removal, reducing the residual porosity inside the ceramic, increasing the relative density of the sintered body, and obtaining a more uniform and dense microstructure. Meanwhile, BaCuB2O5 can improve the grain growth behavior during ceramic sintering, making the microstructure more uniform and reducing local structural defects, thereby reducing dielectric loss caused by porosity and microstructure inhomogeneity. While maintaining the stability of the main Na2B4O7 crystal phase, it improves microwave dielectric properties. The preparation method of the modified microwave dielectric ceramic of this invention, without destroying the main Na2B4O7 crystal phase structure, plays a regulatory role in the microstructure of the ceramic, which is beneficial to promoting material migration and grain boundary bonding during sintering, reducing porosity defects, and making the obtained ceramic material more dense and uniform. It solves the problems of difficult-to-control sintering behavior, high porosity, inhomogeneous microstructure, and weak grain boundary bonding in sodium tetraborate ceramics. The resulting modified microwave dielectric ceramic has a low dielectric constant, low dielectric loss, and good temperature-stable dielectric properties. Experimental results show that the modified microwave dielectric ceramic prepared by the method of this invention has a relative density as high as 89.21%~94.74%; the dielectric properties are: ε... r =3.85~4.87, Q×f=15042~23348GHz, τ f =-38.4~-49.6ppm / ℃, with low dielectric constant, low dielectric loss, and good temperature-stable dielectric properties. Attached Figure Description

[0016] Figure 1 The X-ray diffraction patterns of the modified microwave dielectric ceramics prepared in Examples 1-5 of this invention are shown below. Figure 2 The images shown are SEM images of the modified microwave dielectric ceramics prepared in Examples 1-5 of this invention. Detailed Implementation

[0017] This invention provides a method for preparing modified microwave dielectric ceramics, comprising the following steps: Na2B4O7 and BaCuB2O5 were ball-milled and mixed to obtain a mixed powder; The mixed powder is mixed with a binder and then granulated and extruded sequentially to obtain a ceramic green body. The ceramic blank is sintered to obtain a modified microwave dielectric ceramic.

[0018] In this invention, Na2B4O7 and BaCuB2O5 are ball-milled and mixed to obtain a mixed powder.

[0019] In one embodiment of the present invention, the Na2B4O7 can be obtained by sintering a mixture of H3BO3 and Na2CO3; the molar ratio of H3BO3 to Na2CO3 can be 1:4; the mixing method can be wet ball milling, and the wet ball milling time can be 6-12 hours or 8-12 hours; the grinding media of the wet ball milling can be zirconia balls, and the liquid dispersion solvent of the wet ball milling can be anhydrous ethanol; the ratio of the total mass of H3BO3 and Na2CO3 to the mass of the grinding media and the liquid dispersion solvent can be (0.5-2):(2-5):(1-4) or (1-2):(3-5):(2.5-4); after mixing, the mixture can be dried and sieved sequentially; the drying temperature can be 75-85°C, the degree of drying can be drying to constant weight, and the particle size after sieving can be 80-100 mesh; the sintering temperature can be 500-600°C, and the sintering time can be 9-11 hours.

[0020] In one embodiment of the present invention, the BaCuB2O5 can be obtained by sintering a mixture of Ba(OH)2·H2O, CuO, and H2BO3; the molar ratio of Ba(OH)2·H2O, CuO, and H2BO3 can be 1:1:2; the mixing method can be wet ball milling, and the wet ball milling time can be 6~12h or 8~12h; the grinding medium of the wet ball milling can be zirconia balls, and the liquid dispersion solvent of the wet ball milling can be anhydrous ethanol; the Ba(OH)2 The ratio of the total mass of H2O, CuO, and H2BO3 to the mass of the grinding media and the liquid dispersion solvent can be (0.5~2):(2~5):(1~4) or (1~2):(3~5):(2.5~4); after mixing, the mixture can be dried and sieved sequentially. The drying temperature can be 75~85℃, the degree of drying can be drying to constant weight, and the particle size after sieving can be 80~100 mesh; the sintering temperature can be 750~850℃, and the sintering time can be 9~11h.

[0021] In this invention, the mass of BaCuB2O5 is preferably 1% to 5% of Na2B4O7; as one embodiment of this invention, the mass of BaCuB2O5 can be 1%, 2%, 3%, 4%, or 5% of Na2B4O7. The introduction of the above-mentioned BaCuB2O5 modifying component results in better process stability during sintering, helps alleviate problems such as narrow sintering temperature window, easy softening or deformation of sodium tetraborate during sintering, and improves the controllability and repeatability of the preparation process. The introduction of the above-mentioned BaCuB2O5 modifying component promotes material migration and grain boundary bonding during sintering, reduces porosity defects, and makes the resulting modified microwave dielectric ceramic structure more dense and uniform, thereby improving the structural integrity of the modified microwave dielectric ceramic. This results in a modified microwave dielectric ceramic with low dielectric constant, low dielectric loss, and good temperature-stable dielectric properties. An appropriate amount of BaCuB2O5 can improve grain growth behavior during ceramic sintering, resulting in a more uniform microstructure and reduced local defects. This reduces dielectric loss caused by porosity and microstructure inhomogeneity, and improves microwave dielectric properties while maintaining the stability of the Na2B4O7 bulk crystal phase. However, when the amount of BaCuB2O5 exceeds the optimal range, an increase in the liquid phase formed during sintering may lead to a decrease in local microstructure uniformity, hindering further optimization of the ceramic microstructure and adversely affecting dielectric properties.

[0022] In this invention, the ball milling mixing method is preferably wet ball milling, and the wet ball milling time is preferably 6-12 hours, more preferably 8-12 hours. As one embodiment of this invention, the grinding media for the wet ball milling can be zirconia balls, the liquid dispersion solvent for the wet ball milling can be anhydrous ethanol, and the ratio of the total mass of Na₂B₄O₇ and BaCuB₂O₅ to the mass of the grinding media and the liquid dispersion solvent can be (0.5-2):(2-5):(1-4), or (1-2):(3-5):(2.5-4). These ball milling conditions facilitate thorough mixing and particle refinement of BaCuB₂O₅ and Na₂B₄O₇, increase the specific surface area, and reduce the sintering temperature of the modified microwave dielectric ceramic.

[0023] After ball milling and mixing, the present invention preferably involves drying and sieving the ball-milled product sequentially to obtain a mixed powder. In one embodiment of the present invention, the drying temperature can be 75-85°C, the drying degree can be drying to constant weight, and the particle size after sieving can be 80-100 mesh. The above drying conditions can remove the liquid dispersion solvent added during ball milling, remove moisture from the powder, and obtain a dry and loose powder. The above sieving conditions can control the particle size.

[0024] After obtaining the mixed powder, the present invention mixes the mixed powder with a binder and then granulates and extrudes it sequentially to obtain a ceramic green body.

[0025] In this invention, the binder is preferably a polyvinyl alcohol aqueous solution with a mass fraction of 3-8%, and the mass of the binder is preferably 6-10% of the mixed powder.

[0026] In one embodiment of the present invention, the granulation can be performed by sequentially grinding and sieving the mixed powder and the binder mixture; the grinding is performed until there are no obvious agglomerates and the powder is in a uniform and loose state; the sieving is performed by passing through an 80-mesh standard sieve; in another embodiment of the present invention, the extrusion molding can be performed by placing the granulated product into a molding die and applying pressure to form a ceramic green body; in an embodiment of the present invention, the diameter of the molding die is 12.7 mm, the applied pressure is 40 MPa, and the diameter of the obtained ceramic green body is 12.7 mm and the thickness is 10 mm.

[0027] After obtaining the ceramic blank, the present invention sinters the ceramic blank to obtain modified microwave dielectric ceramic.

[0028] Before sintering, the ceramic blank is preferably heated and debinded; the heating rate is preferably 1~3℃ / min; the debinding temperature is preferably 490~510℃; and the debinding time is preferably 1.5~2.5h.

[0029] After the binder is removed, the present invention preferably does not perform cooling and directly heats up for sintering; the heating rate is preferably 3~5℃ / min; the sintering temperature is preferably 580~620℃; and the sintering time is preferably 3~5h. The above sintering regime can promote the full densification of the ceramic. During the sintering process, BaCuB2O5, due to its low melting temperature, can form a small amount of liquid phase at the sintering temperature, thereby promoting contact, rearrangement, and mass migration between particles, increasing the sintering driving force, and accelerating the sintering densification process of the ceramic. The presence of the liquid phase is beneficial for filling the pores between particles, promoting pore removal, reducing the residual porosity inside the ceramic, increasing the relative density of the sintered body, and obtaining a more uniform and dense microstructure.

[0030] The method for preparing modified microwave dielectric ceramics provided by this invention introduces BaCuB2O5 as a modifying component into a ceramic system with Na2B4O7 as the main crystalline phase. Without destroying the main crystalline phase structure of Na2B4O7, it plays a regulatory role in the microstructure of the ceramic, which is beneficial to promoting material migration and grain boundary bonding during sintering, reducing porosity defects, and making the resulting ceramic material more dense and uniform. It can produce modified microwave dielectric ceramics with low dielectric constant, low dielectric loss, and good temperature-stable dielectric properties.

[0031] The present invention also provides a modified microwave dielectric ceramic prepared by the preparation method described above, comprising Na2B4O7 and BaCuB2O5; wherein Na2B4O7 is the main crystalline phase and BaCuB2O5 is the second phase.

[0032] The modified microwave dielectric ceramic of the present invention comprises Na2B4O7, wherein Na2B4O7 is the main crystalline phase. The Na2B4O7 main crystalline phase belongs to the triclinic crystal system, with boron-oxygen polyhedra as its basic framework building units. This framework is composed of [BO3] triangles, [BO4] tetrahedra, and [NaO6] octahedra. These polyhedral structures are interconnected through oxygen atoms sharing vertices, constructing a complex layered network architecture with low dielectric constant and good high-frequency response characteristics.

[0033] The modified microwave dielectric ceramic of the present invention also includes BaCuB2O5, which is a second phase. As a low-melting-point sintering aid, BaCuB2O5 forms a small amount of liquid phase during sintering without altering the main crystal structure of Na2B4O7. This promotes the contact, rearrangement, and mass migration of the main crystal phase particles, increasing the sintering driving force, thereby reducing the internal porosity of the ceramic and improving its sintering density. Simultaneously, an appropriate amount of BaCuB2O5 helps improve the uniformity of the ceramic microstructure, resulting in more uniform grain size after sintering, further reducing dielectric loss, increasing the product of quality factor and frequency (Q×f), and maintaining a low dielectric constant and good temperature stability.

[0034] In this invention, the grain size of BaCuB2O5 is preferably 0.5~5μm, more preferably 1~3μm.

[0035] The modified microwave dielectric ceramic provided by this invention has a dense and uniform structure, few pore defects, strong grain boundary bonding ability, high relative density, low dielectric constant, low dielectric loss, and good temperature-stable dielectric properties.

[0036] The present invention also provides modified microwave dielectric ceramics prepared by the preparation method described above, or the application of modified microwave dielectric ceramics described above in microwave dielectric devices.

[0037] This invention has no special limitations on its application and can be used in conventional microwave dielectric devices.

[0038] The technical solutions of this invention will be clearly and completely described below with reference to the embodiments thereof. Obviously, the described embodiments are only a part of the embodiments of this invention, and not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without creative effort are within the scope of protection of this invention.

[0039] Example 1 Modified microwave dielectric ceramic: composed of Na2B4O7 and BaCuB2O5; Na2B4O7 is the main crystalline phase, and BaCuB2O5 is the second phase; the mass of BaCuB2O5 is 1% of Na2B4O7, and the grain size of BaCuB2O5 is 1~3μm.

[0040] The preparation method of the modified microwave dielectric ceramic is as follows: Na2B4O7 is weighed and mixed with 1% (by mass) BaCuB2O5 of Na2B4O7. This mixture is then placed in a ball mill with zirconia balls and anhydrous ethanol at a ratio of 1:3:2.5 and wet-milled for 8 hours. After milling, the mixture is dried and sieved sequentially. The drying temperature is 80℃ until constant weight is achieved, and the powder is dispersed through an 80-mesh sieve to obtain a mixed powder. The mixed powder is then mixed with 10% (by mass) of a binder (5% by mass of polyethylene). The mixture of alcohol and aqueous solution is ground sequentially (until there are no obvious agglomerates and the powder is uniformly loose) and sieved through an 80-mesh standard sieve. A ceramic green body is formed by applying a pressure of 40 MPa in a molding mold with a diameter of 12.7 mm. The diameter of the obtained ceramic green body is 12.7 mm and the thickness is 10 mm. The ceramic green body is heated to 500 °C at a heating rate of 3 °C / min and held for 2 h to remove the binder. Then, it is sintered at 600 °C at a heating rate of 5 °C / min for 3 h to obtain modified microwave dielectric ceramic. Preparation method of Na2B4O7: H3BO3 and Na2CO3 are weighed and mixed in a molar ratio of 1:4. The mixture is then placed in a ball mill with zirconium oxide balls and anhydrous ethanol in a ratio of 1:3:2.5 for wet ball milling for 8 hours. After ball milling, the mixture is dried and sieved sequentially. The drying temperature is 80℃ and the mixture is dried to constant weight. The mixture is then dispersed through an 80-mesh sieve and sintered at 500℃ for 10 hours. Preparation method of BaCuB2O5: Ba(OH)2·H2O, CuO and H2BO3 are weighed and mixed in a molar ratio of 1:1:2. This mixture is then placed in a ball mill with zirconium oxide balls and anhydrous ethanol in a ratio of 1:3:2.5 for wet ball milling for 8 hours. After ball milling, the mixture is dried and sieved sequentially. The drying temperature is 80℃ until constant weight is achieved. The mixture is then dispersed through an 80-mesh sieve and sintered at 800℃ for 10 hours.

[0041] Example 2 Modified microwave dielectric ceramic: composed of Na2B4O7 and BaCuB2O5; Na2B4O7 is the main crystalline phase, and BaCuB2O5 is the second phase; the mass of BaCuB2O5 is 2% of Na2B4O7, and the grain size of BaCuB2O5 is 1~3μm.

[0042] The preparation method of the modified microwave dielectric ceramic is different from that of Example 1 only in that "weighing and mixing Na2B4O7 with 1% of Na2B4O7 by mass of BaCuB2O5" is replaced with "weighing and mixing Na2B4O7 with 2% of Na2B4O7 by mass of BaCuB2O5". The preparation method of Na2B4O7 is the same as in Example 1; The preparation method of BaCuB2O5 is the same as in Example 1.

[0043] Example 3 Modified microwave dielectric ceramic: composed of Na2B4O7 and BaCuB2O5; Na2B4O7 is the main crystalline phase, and BaCuB2O5 is the second phase; the mass of BaCuB2O5 is 3% of Na2B4O7, and the grain size of BaCuB2O5 is 1~3μm.

[0044] The preparation method of the modified microwave dielectric ceramic is different from that of Example 1 only in that "weighing and mixing Na2B4O7 with 1% of Na2B4O7 by mass of BaCuB2O5" is replaced with "weighing and mixing Na2B4O7 with 3% of Na2B4O7 by mass of BaCuB2O5". The preparation method of Na2B4O7 is the same as in Example 1; The preparation method of BaCuB2O5 is the same as in Example 1.

[0045] Example 4 Modified microwave dielectric ceramic: composed of Na2B4O7 and BaCuB2O5; Na2B4O7 is the main crystalline phase, and BaCuB2O5 is the second phase; the mass of BaCuB2O5 is 4% of Na2B4O7, and the grain size of BaCuB2O5 is 1~3μm.

[0046] The preparation method of the modified microwave dielectric ceramic is different from that of Example 1 only in that "weighing and mixing Na2B4O7 with 1% of Na2B4O7 by mass of BaCuB2O5" is replaced with "weighing and mixing Na2B4O7 with 4% of Na2B4O7 by mass of BaCuB2O5". The preparation method of Na2B4O7 is the same as in Example 1; The preparation method of BaCuB2O5 is the same as in Example 1.

[0047] Example 5 Modified microwave dielectric ceramic: composed of Na2B4O7 and BaCuB2O5; Na2B4O7 is the main crystalline phase, and BaCuB2O5 is the second phase; the mass of BaCuB2O5 is 5% of Na2B4O7, and the grain size of BaCuB2O5 is 1~3μm.

[0048] The preparation method of the modified microwave dielectric ceramic is different from that of Example 1 only in that "weighing and mixing Na2B4O7 with 1% of Na2B4O7 by mass of BaCuB2O5" is replaced with "weighing and mixing Na2B4O7 with 5% of Na2B4O7 by mass of BaCuB2O5". The preparation method of Na2B4O7 is the same as in Example 1; The preparation method of BaCuB2O5 is the same as in Example 1.

[0049] Comparative Example 1 Microwave dielectric ceramic: composed of Na2B4O7; Na2B4O7 is the main crystalline phase.

[0050] The preparation method of the modified microwave dielectric ceramic is different from that of Example 1 only in that "weighing and mixing Na2B4O7 with 1% BaCuB2O5 of Na2B4O7 by mass" is replaced with "Na2B4O7". The preparation method of Na2B4O7 is the same as in Example 1.

[0051] X-ray diffraction analysis was performed on the modified microwave dielectric ceramics prepared in Examples 1-5 of this invention, and the obtained X-ray diffraction (XRD) patterns are as follows. Figure 1 As shown, Figure 1 In this context, 1wt.%BCB, 2wt.%BCB, 3wt.%BCB, 4wt.%BCB, and 5wt.%BCB represent Examples 1, 2, 3, 4, and 5, respectively. Figure 1 As can be seen, the main diffraction peaks of the samples are basically consistent with the standard diffraction peaks of Na2B4O7, indicating that Na2B4O7 is the main crystalline phase of the ceramic. Weaker diffraction peaks were observed at 2θ = 17.1° and 19.6°, corresponding to the standard diffraction peaks of BaCuB2O5, indicating the presence of a small amount of BaCuB2O5 as a second phase in the samples. As the amount of BaCuB2O5 added increased from 1 wt.% to 5 wt.%, the positions of the main diffraction peaks in the samples from each embodiment remained basically consistent, and no significant change in the main crystal orientation was observed. This indicates that the addition of BaCuB2O5 did not change the main crystal structure of Na2B4O7, but rather it mainly existed as a second phase.

[0052] The modified microwave dielectric ceramics prepared in Examples 1-5 of this invention were subjected to scanning electron microscopy (SEM) for micromorphological analysis. The obtained SEM images are shown below. Figure 2 As shown, Figure 2 In the figures (a), (b), (c), (d), and (e), they represent Examples 1, 2, 3, 4, and 5, respectively. Combined with XRD analysis results, it can be seen that Na₂B₄O₇ is the main crystalline phase, while BaCuB₂O₅ exists as a trace amount of the second phase. Specifically, with the change in the amount of BaCuB₂O₅ added, the ceramic matrix exhibits a clear densification evolution pattern: when the amount added is low (Examples 1, 2, ...), ... Figure 2 (a) and (b)) a certain number of residual pores still exist inside the ceramic, and the density of the structure is relatively low; when the addition amount is optimized to 3% of the mass of BaCuB2O5 as Na2B4O7 (Example 3), Figure 2 c) The microstructure exhibits optimal continuity and density, with pores essentially eliminated, indicating that this addition amount is beneficial for promoting ceramic sintering and microstructural densification; however, with further increases in the addition amount (Examples 4 and 5), Figure 2 (d) and (e) show rough tissue and a few dark areas in some local areas.

[0053] Density tests were performed on the modified microwave dielectric ceramics prepared in Examples 1-5 of the present invention and the microwave dielectric ceramics prepared in Comparative Example 1. The theoretical density was calculated based on the cell structure data, the volume density was measured by Archimedes' exclusion method, and the relative density was obtained by dividing the volume density by the theoretical density. The results are shown in Table 1.

[0054] Table 1 Density test results

[0055] As can be seen from the density test results in Table 1, with the increase of BaCuB2O5 addition, the theoretical density of the sample increased from 2.367 g / cm³. 3 Gradually increased to 2.422 g / cm³ 3 Meanwhile, the volumetric density and relative density of the samples showed a trend of first increasing and then decreasing. In Example 3 (BaCuB2O5 addition amount was 3wt%), the volumetric density and relative density reached their maximum values ​​of 2.274 g / cm³. 3 The relative density was 94.74%, indicating that the sample had the optimal degree of densification at this point. Further increasing the amount of BaCuB2O5 added resulted in a slight decrease in relative density, suggesting that the addition of an appropriate amount of BaCuB2O5 is beneficial for promoting the sintering densification of the modified microwave dielectric ceramic, while excessive addition is not conducive to further improving the densification level of the material. The relative density test results of each embodiment are highly consistent with the above-described microstructure change patterns.

[0056] The dielectric properties of the modified microwave dielectric ceramics prepared in Examples 1-5 of the present invention and the microwave dielectric ceramics prepared in Comparative Example 1 were tested (measured using the parallel plate method by PNA-X N5244A vector network analysis), and the results are shown in Table 2.

[0057] Table 2 Dielectric property test results

[0058] As can be seen from Table 2, the modified microwave dielectric ceramics prepared in Examples 1-5 have lower dielectric constants, lower dielectric losses, and better temperature-stable dielectric properties compared to the microwave dielectric ceramics in Comparative Example 1.

[0059] As can be seen from the above embodiments, the modified microwave dielectric ceramic prepared by the method of the present invention is composed of Na₂B₄O₇ and BaCuB₂O₅. Na₂B₄O₇ is the main crystalline phase, while BaCuB₂O₅ exists as a trace amount of the second phase. It exhibits high relative density, low dielectric constant, low dielectric loss, and good temperature-stable dielectric properties. BaCuB₂O₅ has a low melting temperature and can form a small amount of liquid phase during sintering, promoting particle rearrangement and mass migration, increasing sintering driving force, accelerating ceramic densification, and reducing internal porosity. Simultaneously, an appropriate amount of BaCuB₂O₅ helps improve the uniformity of the ceramic microstructure, increases the relative density of the sintered body, thereby reducing dielectric loss and improving microwave dielectric properties.

[0060] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A method for preparing modified microwave dielectric ceramics, comprising the following steps: Na2B4O7 and BaCuB2O5 were ball-milled and mixed to obtain a mixed powder; The mixed powder is mixed with a binder and then granulated and extruded sequentially to obtain a ceramic green body. The ceramic blank is sintered to obtain a modified microwave dielectric ceramic.

2. The preparation method according to claim 1, characterized in that, The mass of BaCuB2O5 is 1% to 5% of that of Na2B4O7.

3. The preparation method according to claim 1, characterized in that, The particle size of the mixed powder is 80-100 mesh.

4. The preparation method according to claim 1, characterized in that, The sintering temperature is 580~620℃, and the sintering time is 3~5h.

5. The preparation method according to claim 1 or 4, characterized in that, Before sintering, the adhesive is removed by heating. The temperature for removing the adhesive is 490~510℃ and the time for removing the adhesive is 1.5~2.5h.

6. The preparation method according to claim 1, characterized in that, The adhesive is a polyvinyl alcohol aqueous solution with a mass fraction of 3-8%.

7. The preparation method according to claim 6, characterized in that, The mass of the binder is 6-10% of the mixed powder.

8. The modified microwave dielectric ceramic prepared by the preparation method according to any one of claims 1 to 7, comprising Na2B4O7 and BaCuB2O5; wherein Na2B4O7 is the main crystalline phase and BaCuB2O5 is the second phase.

9. The modified microwave dielectric ceramic according to claim 8, characterized in that, The grain size of the BaCuB2O5 is 0.5~5μm.

10. The application of the modified microwave dielectric ceramic prepared by the preparation method according to any one of claims 1 to 7 or the modified microwave dielectric ceramic according to any one of claims 8 to 9 in microwave dielectric devices.